Hubungan Perilaku Kesehatan dengan Kejadian Demam Berdarah Dengue (DBD) di Wilayah Kerja Puskesmas Ma. Kumpeh Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi - Rosdawati Rosdawati (Jurnal Akademika Baiturrahim Jambi, 2021)
The incidence of Dengue Hemorrhagic Fever (DHF) in the working area of Puskesmas Ma. Kumpeh in 2019 recorded as many as 73 cases with 1 victim died. The data obtained shows that there is a significant increase in the incidence of Dengue Hemorrhagic Fever from year to year between 2015-2019. The purpose of this study was to determine what health behaviors are associated with the occurrence of Dengue Hemorrhagic Fever (DHF) in the working area of Puskesmas Ma. Kumpeh Kumpeh Ulu Subdistrict, Muaro Jambi Regency. This type of research is an analytic survey using a case-control approach. The population of this study were Dengue Hemorrhagic Fever sufferers (cases) and not Dengue Hemorrhagic Fever sufferers (controls). A sample of 40 cases and 40 controls was obtained using simple random sampling technique. The instrument used was a questionnaire. Data were analyzed using Chi-square statistical test and determination of Odds Ratio (OR). The results showed that there was a relationship between health behavior and the incidence of Dengue Hemorrhagic Fever (DHF) in the Puskesmas Ma area. Kumpe in 2020, namely cleaning water reservoirs, closing water reservoirs, draining water reservoirs, burying used goods, disposing of garbage in its place and burning it, hanging clothes, and wearing mosquito repellent lotions. It is advisable for health workers to pay more attention to health behavior or daily habits because they are important in the transmission and spread of DHF and need further research.